Stock markets and the COVID-19 fractal contagion effects - Okorie, David Iheke; Lin, Boqiang (Finance research letters, 2021)
•This paper investigates the fractal contagion effects of COVID-19 on the Stock Markets.•The DMCA and DCCA techniques are used to test the fractal contagion hypothesis.•Found significant fractal contagion effects on the stock markets return and volatility.•The COVID-19 fractal contagion effects on the stock market fizzle over the medium and long time horizons. This article investigates the fractal contagion effect of the COVID-19 pandemic on the stock markets. The stock market information of the top 32 coronavirus affected economies (as of 31st March 2020) was sampled for ex-ante and ex-post COVID-19 outbreak analysis using the Detrended Moving Cross-Correlation Analysis (DMCA) and Detrended Cross-Correlation Analysis (DCCA) techniques. The results confirm a fractal contagion effect of the COVID-19 pandemic on the stock markets. Furthermore, this fractal contagion effect fizzles out over time (in the middle and long run) for both the stock markets return and volatility. Therefore, this article provides pieces of evidence for the COVID-19 fractal contagion effect on the stock markets.